Life goals and gender differences among chronically homeless individuals entering permanent supportive housing. Issue 1 (2nd January 2017) - Bird, Melissa; Rhoades, Harmony; Lahey, John; Cederbaum, Julie; Wenzel, Suzanne
ABSTRACT: This research seeks to understand goals and the gender differences in goals among men and women who are transitioning into permanent supportive housing. Men and women experience homelessness differently. Data collected for this study come from a longitudinal investigation of HIV risk behavior and social networks among women and men transitioning from homelessness to permanent supportive housing. As part of this study, 421 baseline interviews were conducted in English with homeless adults scheduled to move into permanent supportive housing; participants were recruited between September 2014 and October 2015. This paper uses goals data from the 418 male-or female-identified respondents in this study. Results identified goal differences in education and general health between men and women that should be taken into account when service providers, policy makers, and advocates are addressing the needs of homeless women.